Clinical profile of female patients with chronic telogen effluvium and its association with serum ferritin level - Minu Sunil,; Meriya Zacharia, (Asian Journal of Medical Sciences, 2024)
Background: Diffuse hair loss persisting longer than 6 months without any cause is referred to as chronic telogen effluvium (CTE). The role of iron deficiency without anemia in causing chronic diffuse hair loss is unclear. Some studies have reported a critical threshold of 40 mcg/mL of serum ferritin, below which increased telogen shedding was observed. Screening all patients with CTE for iron deficiency will aid us in finding a possible cause and help in its management. Aims and Objectives: To study the clinico-epidemiological profile of female patients with CTE and its association with serum ferritin levels. Materials and Methods: Cross-sectional study on 263 female patients aged 13–60 years with CTE attending the Department of Dermatology at Government Medical College, Kottayam. Results: The mean age of patients with CTE was 28.92 years. Trichodynia was reported by 20% among which 70% reported associated mental stress which was statistically significant. Bitemporal thinning was noted in 57% and 68% had short growing hairs in the frontal/bitemporal region. The hair pull test was positive in 37.6%, high visual analog grade of hair loss in 92%. Only 32% had anemia (Hb <12) but 86% had S. ferritin <40 mcg/L with the mean S. ferritin being 23.93 ng/mL and the majority were in the age group of 20–29 years. Conclusion: The majority were found to have low serum ferritin levels without clinical anemia, which could indicate an association between low iron stores and CTE. Additional case–control studies are needed to establish the role of iron deficiency in causing hair loss.